Passively Q-switched Ytterbium doped fiber laser with mechanically exfoliated MoS2 saturable absorber - Al-Masoodi, Ahmed Hasan Hamood; Ahmed, Mahmoud Hazzaa M.; Latiff, Anas Abdul; Arof, Hamzah; Harun, Sulaiman Wadi (Springer Verlag (Germany), 2017)
A passively Q-switched Ytterbium-doped fiber laser (YDFL) based on MoS2 saturable absorber (SA) is demonstrated. A few layers of MoS2 are mechanically exfoliated from a natural MoS2 crystal using a scotch tape and the resulting SA is sandwiched between two fiber ferrules to form a fiber compatible Q-switcher. The saturation intensity, non-saturable intensity, and modulation depth of the MoS2 SA are 23.5 MW/cm2, 23.0, and 11.3%, respectively. By introducing the MoS2 SA into the YDFL cavity, a stable pulse laser is generated at 1070.2 nm wavelength with a threshold pump power of 49.57 mW. The repetition rate of the Q-switched pulses ranges from 3.817 to 25.25 kHz, as the 980 nm pump power increases from 49.57 to 87.2 mW. The highest pulse energy is 295.45 nJ at a pump power of 87.2 mW.